(untitled) (Journal of Informatics Education and Research, 2023)
The burgeoning presence of social media platforms has substantially recalibrated the dynamics of fashion consumption, particularly among millennial. This demographic group, intrinsically linked with the digital landscape, experiences a plethora of influences that govern their buying behavior towards fashion apparels. The nexus of social media platforms and millennial has given rise to nuanced forms of marketing, including influencer partnerships and tailored advertisements, which intricately mold their purchasing preferences. Furthermore, these platforms have become arenas where brand narratives unfold, weaving a complex tapestry of engagement, persuasion, and consumer decisions. Peer reviews and community discussions further enrich this tapestry, offering a robust ground of trust and validation that millennial heavily rely on before making a purchase. The social media wields on the buying behaviour of millennial in the context of fashion apparels, delineating the pathways through which virtual interactions transmute into real-world purchasing decisions.